Cyperus entrerianus Boeckeler, a new record from Vietnam - Nha, Phan Thi Thanh; Tuan, Dang Le Anh (Academia Journal of Biology, 2020)
Cyperus entrerianus Boeckeler, an invasive alien plant from South America, is newly recorded from Vietnam. A morphological description, color illustrations, line drawings and distinguishable morphological characters of C. entrerianus from C. surinamensis and C. luzulae were provided, additionally and short notes, and habitat of the species were also given.